Gut immune cells—A novel therapeutical target for cardiovascular disease? - Naresh Ganesh; Emiel P. C. van der Vorst; Emiel P. C. van der Vorst; Emiel P. C. van der Vorst; Jens Spiesshöfer; Shun He; Mathias Burgmaier; Hannes Findeisen; Michael Lehrke; Filip K. Swirski; Nikolaus Marx; Florian Kahles (Frontiers in Cardiovascular Medicine, 2022)
Despite scientific and clinical advances during the last 50 years cardiovascular disease continues to be the main cause of death worldwide. Especially patients with diabetes display a massive increased cardiovascular risk compared to patients without diabetes. Over the last two decades we have learned that cardiometabolic and cardiovascular diseases are driven by inflammation. Despite the fact that the gastrointestinal tract is one of the largest leukocyte reservoirs of our bodies, the relevance of gut immune cells for cardiovascular disease is largely unknown. First experimental evidence suggests an important relevance of immune cells in the intestinal tract for the development of metabolic and cardiovascular disease in mice. Mice specifically lacking gut immune cells are protected against obesity, diabetes, hypertension and atherosclerosis. Importantly antibody mediated inhibition of leukocyte homing into the gut showed similar protective metabolic and cardiovascular effects. Targeting gut immune cells might open novel therapeutic approaches for the treatment of cardiometabolic and cardiovascular diseases.